LAW ENFORCEMENT AGAINST CORRUPTION IN INDONESIA: BETWEEN EXPECTATION AND REALITY - Agus Salim; Suryati Suryati; Ruslan Yusoh (Sabtida, 2025)
This study critically examines the effectiveness of law enforcement efforts against corruption in Indonesia, highlighting the persistent gap between legal expectations and practical outcomes. Despite a comprehensive legal framework including Law No. 31/1999, Law No. 20/2001, and the establishment of the Corruption Eradication Commission (KPK) Key Alta institutions continue to face political interference, limited resources, legal loopholes, and inconsistent prosecutorial practices. For example, underscore that although asset recovery and conviction rates have risen, sentencing disparities and institutional constraints remain prevalent, impeding deterrence. Complementing this, identifies political coercion and inadequate capacity at enforcement bodies such as the KPK, police, and judiciary as key impediments. This research employs a normative-juridical method, reviewing legislation, judicial rulings, and institutional practices. It also integrates recent Scopus-indexed empirical studies to strengthen its analytical framework. The findings reveal that while recent innovations such as digital oversight in public procurement have improved transparency and stakeholder engagement, they have not yet substantially closed enforcement gaps. The study concludes that sustainable progress requires enhancing institutional independence, ensuring sufficient funding and resources, tightening legal provisions, fostering judicial reform, and embracing innovative approaches such as e‑procurement systems and civil society oversight. These measures are essential to bridging the divide between aspirations and reality in Indonesia's anti‑corruption enforcement mechanisms, thereby meeting both domestic expectations and global standards.